Discovery of very high energy γ-ray emission from the BL Lacertae object PKS 0301-243 with H.E.S.S. - Abramowski, A. (2013)
The active galactic nucleus PKS 0301−243 (z = 0.266) is a high-synchrotron-peaked BL Lac object that is detected at high energies (HE, 100 MeV <E < 100 GeV) by Fermi/LAT. This paper reports on the discovery of PKS 0301−243 at very high energies (E > 100 GeV) by the High Energy Stereoscopic System (H.E.S.S.) from observations between September 2009 and December 2011 for a total live time of 34.9 h. Gamma rays above 200 GeV are detected at a significance of 9.4σ. A hint of variability at the 2.5σ level is found. An integral flux I(E > 200 GeV) = (3.3 ± 1.1stat ± 0.7syst) × 10-12 ph cm-2 s-1 and a photon index Γ = 4.6 ± 0.7stat ± 0.2syst are measured. Multi-wavelength light curves in HE, X-ray and optical bands show strong variability, and a minimal variability timescale of eight days is estimated from the optical light curve. A single-zone leptonic synchrotron self-Compton scenario satisfactorily reproduces the multi-wavelength data. In this model, the emitting region is out of equipartition and the jet is particle dominated. Because of its high redshift compared to other sources observed at TeV energies, the very high energy emission from PKS 0301−243 is attenuated by the extragalactic background light (EBL) and the measured spectrum is used to derive an upper limit on the opacity of the EBL.